NILAI-NILAI PENDIDIKAN TOLERANSI RASULULLAH DENGAN NON MUSLIM - Ahmad Hifdzil Haq; Suprapno Suprapno; Adisel Adisel; Moch Iqbal; Riswanto Riswanto (STAI Tuanku Tambusai, 2022)
Tolerance is a value that is very familiar to us as Indonesian citizens who are multicultural, with various ethnicities, cultures, languages and religions. But not infrequently we as Muslims have not been able to place its meaning proportionally. This paper aims to reveal how the Prophet taught tolerance towards non-Muslims. The method used in this article is the library method. The results presented are that Islamic tolerance lies in the concept of